2014
DOI: 10.1021/jf504461c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dilute Acid and Sulfite Pretreatments onAcacia confusafor Biofuel Application and the Influence of Its Extractives

Abstract: Chemical components of lignocellulosic biomass may impede biofuel processing efficiency. To understand whether the heartwood of Acacia confusa is suitable for biofuel application, extractive-free heartwood of A. confusa was subjected to dilute acid (DA) or sulfite pretreatments. Sugar recoveries were used to evaluate the performance of different pretreatments. Cell wall properties, such as 4-O-alkylated lignin structures, S/G ratios, and xylan contents, of the pretreated samples showed significant correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Consequently, the presence of leaf increased the non-carbohydrate constituent and reduced the proportion of convertible sugar in WTC. Additionally, high phenolic content, ash, and extractives in the leaves will have negative impacts on the bioconversion process [39–42]. The leaves appeared to be problematic.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the presence of leaf increased the non-carbohydrate constituent and reduced the proportion of convertible sugar in WTC. Additionally, high phenolic content, ash, and extractives in the leaves will have negative impacts on the bioconversion process [39–42]. The leaves appeared to be problematic.…”
Section: Resultsmentioning
confidence: 99%
“…An unclear correlation has also been reported, such as green liquor and Kraft pretreated Eucalyptus (Papa et al, 2012; Santos et al, 2012), NaOH and H 2 SO 4 pretreated wheat and rice samples (Wu et al, 2013), and mild acid treated maize cell wall (Zhang et al, 2011). When the S/G ratio of the remaining lignin in pretreated biomass is studied, contradictory results also exist: a lesser proportion of non-condensed lignin in the pretreated biomass was reported to be beneficial to biomass hydrolysis as non-condensed lignin (high β- O -4′) tended to be linear shape, likely a higher coverage over cellulose fibers (Zhang et al, 2011; Yeh et al, 2014); by contrast, others found high S/G ratio of lignin in the pretreated biomass was positively correlated with enzymatic digestibility as branched G-lignin gave rise to more physical barrier (Santos et al, 2012; Yu et al, 2014). These inconsistent results suggest that S/G ratio contributes only partially to biomass recalcitrance, and the complexities of biomass species and pretreatment with concomitant other cell wall structure changes likely shelter the effects arising from lignin composition.…”
Section: Lignin Monolignol Compositional Unitsmentioning
confidence: 99%
“…For the Cu-AHP, this is manifested as slightly lower yields for the eucalyptus at low enzyme loadings and shorter hydrolysis times, although the maximum glucose yields (~ 80%) are comparable at the highest enzyme loadings (30 mg/g) and incubation times (72 h). A likely contributor to this higher recalcitrance in the eucalyptus is the higher lignin content (30% by mass) relative to the poplar (24% by mass) as well as potentially the higher extractives content, which are known to inhibit cellulase activity [48] and decrease the efficacy of pretreatment and enzymatic hydrolysis [49]. When similar conditions are compared for the [Ch] [Lys] pretreatment, the poplar gives higher yields for most conditions, presumably due to a combination of the lower intrinsic recalcitrance of the biomass as well as the (unquantified) pretreatment-solubilized inhibitors of hydrolysis.…”
Section: Enzymatic Hydrolysis Yieldsmentioning
confidence: 99%